Peningkatan Kapasitas Belajar Mandiri Siswa melalui Pendekatan Self-directed Learning sebagai Upaya Kesiapan Menuju Pendidikan Tinggi bagi Siswa SMA IT Al-Uswah Surabaya - Fithriyah Cholifatul Ummah; Hilmy Abyan Utama; Sakina; Sherly Yolanda; Samsriyaningsih Handayani; Maftuchah Rochmanti; Hermanto Tri Joewono; Lilik Herawati; Cecilia Felicia Chandra; Evi Fuji Andini (Sewagati, 2026)
Introduction: Independent learning capacity is an essential skill that students must possess in order to face educational challenges. However, students' difficulties in recognizing their potential, managing their study time, and designing independent learning strategies in high school can impact their readiness to enter higher education, which places greater emphasis on adult learning. This Community Service Program (PkM) focuses on developing self-directed learning (SDL) skills. Method: This activity was carried out at SMAIT Al Uswah Surabaya, involving 113 11th grade students and 11th grade teachers. The activity methods included: 1) Socialization and discussion with teachers and students, 2) Training in independent learning skills and SDL-Readiness measurement for students, 3) Development of SDL Modules, 4) Monitoring and Evaluation. Results: The evaluation results showed that SMAIT Al Uswah Surabaya students had a high readiness to apply independent learning skills, with a Mean SDL-Readiness of 114.36 (Cronbach’s alpha: 0.917). Students were also able to learn to recognize their strengths and weaknesses. Digital distractions from social media and a lack of reflective habits were identified as challenges to the application of independent learning. Conclusion: Students have strong potential to become independent learners. Self-reflection skills are necessary to manage the independent learning process effectively. Teachers, as facilitators, play an important role in creating a reflective, collaborative learning environment that supports student autonomy. Keywords: Independent Learning, Higher Education Readiness, Academic Achievement, High School, Self-directed Learning